2001
DOI: 10.1073/pnas.98.3.1194
|View full text |Cite
|
Sign up to set email alerts
|

Lack of type XV collagen causes a skeletal myopathy and cardiovascular defects in mice

Abstract: Type XV collagen occurs widely in the basement membrane zones of tissues, but its function is unknown. To understand the biological role of this protein, a null mutation in the Col15a1 gene was introduced into the germ line of mice. Despite the complete lack of type XV collagen, the mutant mice developed and reproduced normally, and they were indistinguishable from their wild-type littermates. However, Col15a1-deficient mice showed progressive histological changes characteristic for muscular diseases after 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(98 citation statements)
references
References 47 publications
(33 reference statements)
4
91
0
1
Order By: Relevance
“…Primary sequence comparisons of the mouse and human collagen XV genes revealed that the mouse harbors seven collagenous domains to nine for the human gene (23). In addition, although the conserved C-terminal endostatin domain predicts a role in angiogenesis, inactivation of the mouse structural gene by homologous recombination revealed a normal vasculature (24). Taken in sum, these data support the hypothesis that the physiological role of collagen XV is different between the two species.…”
Section: Resultssupporting
confidence: 76%
“…Primary sequence comparisons of the mouse and human collagen XV genes revealed that the mouse harbors seven collagenous domains to nine for the human gene (23). In addition, although the conserved C-terminal endostatin domain predicts a role in angiogenesis, inactivation of the mouse structural gene by homologous recombination revealed a normal vasculature (24). Taken in sum, these data support the hypothesis that the physiological role of collagen XV is different between the two species.…”
Section: Resultssupporting
confidence: 76%
“…Human diseases due to mutations in the collagen XV gene are not known, but mice lacking this collagen have a mild myopathic phenotype, with impaired cardiac and microvascular structure and function (Eklund et al, 2001;Rasi et al, 2010). Thus despite the high structural similarities between collagens XVIII and XV, they have entirely different biological roles.…”
Section: Mutations In Collagen XVIII Lead To Knobloch Syndromementioning
confidence: 98%
“…Proliferation of MPCs generates myoblasts that undergo several rounds of division before fusing to form myofibers, which comprise the basic cellular unit of skeletal muscle. During skeletal muscle regeneration, ECM molecules play a key role in the proliferation of MPCs and myoblasts as well as the subsequent stages of differentiation required to form new myofibers [11][12][13][14][15][16][17]. The study of skeletal muscle ECM regulation of MPC and myoblast behavior presents a significant challenge.…”
Section: Introductionmentioning
confidence: 99%